The improper use of deep-frying oils generates malonaldehyde, a toxic substance for health - Bonilla Mosquera, Nayibe; Pérez Garzón, María Fernanda; Millán Estupiñán, Juan Carlos (DIXI, 2021)
Subject and scope: The aim of this paper was to analyze aldehyde content, specifically malonaldehyde, present in deep-frying oils used in food preparation in Universidad Santiago de Cali, its health effects during 2016-2017 and the transgression of the right to a healthy environment. Characteristics: An observational, descriptive, and cross-sectional study. Univariate and bivariate analysis was conducted. An Epi Info version 7.0 spreadsheet was used. The personnel working in the cafeterias of a higher education institution were interviewed and the constitutional norms were studied. Findings: The study found that there is a slight tendency to obtain higher values ​​in the pH measurements in the case of the new oils used in each of the establishments, but in the measurements of the reused oils, the pH were lower. Also, it is important to note that in any case the pH measurements for new oils were lower than the values ​​for used oils. When conducting the bivariate analysis between the sample mean value and the tba test, it was found that the higher the mean values, the tba test values ​​increased, with a Spearman correlation coefficient of 1 (perfect correlation). Conclusion: The evaluated parameters of pH, color, temperature and tba formation allowed to confirm the change in the qualities of the analyzed oils and the presence of malonaldehyde in the samples collected in the cafeterias and, also, in the replicas obtained in the laboratory, which generates expectations regarding the health of the population and requires decision-making by the institution.